Making Self-Care a Priority for Women At Risk of Breast Cancer–Related Lymphedema. (May 2014) - Radina, M. Elise; Armer, Jane M.; Stewart, Bob R.
Estimates suggest that between 41% and 94% of breast cancer survivors may develop the chronic condition of secondary lymphedema at some point during their lifetimes. Self-care is critical for effective lymphedema management and risk-reduction. At the same time, women in general have been characterized as engaging in self-sacrificing behaviors in which they choose other-care over self-care. This study explored the self-care experiences of women with breast cancer within the contexts of complex and demanding familial and work-related responsibilities. Participants ( N = 14) were enrolled in a behavioral-educational intervention aimed at lymphedema risk-reduction. This feminist family theory-informed secondary analysis of qualitative data focused on women's familial roles and the balance or lack of balance between self-sacrifice and self-care. Findings included participants' struggles with time management and prioritizing self-care over care of others as well as making a commitment to self-care. Findings have implications for patient and family-level education and research with regard to gender role-based barriers to self-care and self-care within complex social contexts.